Glutathione S-transferases Control astrocyte activation and neuronal health during neuroinflammation - Matoba, Ken; Dohi, Eisuke; Choi, Eric Y.; Kano, Shin-ichi (Frontiers in Molecular Biosciences, 2023)
Glutathione S-transferases (GSTs) are phase II detoxification enzymes of xenobiotic metabolism and readily expressed in the brain. Nevertheless, the current knowledge about their roles in the brain is limited. We have recently discovered that GSTM1 promotes the production of pro-inflammatory mediators by astrocytes and enhances microglial activation during acute brain inflammation. Here we report that GSTM1 significantly affects TNF-a-dependent transcriptional program in astrocytes and modulates neuronal activities and stress during brain inflammation. We have found that a reduced expression of GSTM1 in astrocytes downregulates the expression of pro-inflammatory genes while upregulating the expression of genes involved in interferon responses and fatty acid metabolism. Our data also revealed that GSTM1 reduction in astrocytes increased neuronal stress levels, attenuating neuronal activities during LPS-induced brain inflammation. Furthermore, we found that GSTM1 expression increased in the frontal cortex and hippocampus of aging mice. Thus, this study has further advanced our understanding of the role of GSTs in astrocytes during brain inflammation and paved the way for future studies to determine the critical role of GSTM1 in reactive astrocyte responses in inflammation and aging.